PENDIDIKAN NILAI MORAL DITINJAU DARI PERSPEKTIF GLOBAL - Sudiati Sudiati (Jurnal Cakrawala Pendidikan, 2009)
AbstractMoral value education is both a demand and a need for human beings as amanifestation of togetherness in terms of nations and countries with a variety ofproblems. There are a lot of problems, such as global terrorism andmultidimensional crises, which one country cannot solve on its own because to doso it needs other countries supports. Moral value education is an alternativeproblem solution which is local, regional, national, and international in nature. Ithas become a global issue in several countries (Indonesia, Malaysia, India, andChina) and it has some differences and similarities. The differences result from thecountries different ideologies. However, such countries emphasize moral valueeducation on moral ethic values, especially on values related to human rights thatare universal and global in nature. The concept of moral value education proposedby Kohlberg and Miller tends to be individualistic. Therefore, its needs to becomplemented by taking account of the paradigm proposed by Capra that humanlife is built on the basis of a systemic and holistic view of life, one which is notpartial and individualistic. In its implementation, it needs an appropriate approachand a relevant method and technique. The approaches to moral value educationinclude inculcating, modelling, facilitating, and skill development approaches, andthe methods include dogmatic, deductive, inductive, and reflective methods.Keywords: moral value education, global perspective